Pengembangan Perpustakaan Desa Dalam Peningkatan Budaya Literasi Masyarakat Desa Penembang Kabupaten Bengkulu Tengah - Lailatus Sa'diyah; Fransiska Timoria Samosir; Diyas Widiyarti (Manhaj: Jurnal Penelitian dan Pengabdian Masyarakat, 2023)
The low condition of community literacy is characterized by the lack of book reading activities compared to other activities, the inadequate allocation of time to reading books, the small number of book collections, the lack of allocation of funds to buy books, and low visits to libraries and bookstores. The role of village libraries is necessary for supporting the improvement of community literacy culture, especially in areas with limited access to information sources. Village libraries also have an essential role in efforts to alleviate illiteracy, especially in rural communities. This service activity aims to optimize village libraries' management in Penembang Village, Bengkulu Tengah, and provide training to village library managers on effective village library management according to village library management standards. The method of implementing this activity includes procuring library material collections, providing reading facilities, and conducting training on village library management. The result of this activity is the availability of library collections, room design, and library management training. In improving village library services, the service team participated in adding a collection of books.